Chemical Constituents, Antifungal and Antioxidative Effects of Ajwain Essential Oil and Its Acetone Extract - Singh, Gurdip (2004)
GC and GC-MS analysis of ajwain essential oil showed the presence of 26 identified components which account for 96.3% of the total amount. Thymol (39.1%) was found as a major component along with p-cymene (30.8%), γ-terpinene (23.2%), β-pinene (1.7%), terpinene-4-ol (0.8%) whereas acetone extract of ajwain showed the presence of 18 identified components which account for 68.8% of the total amount. The major component was thymol (39.1%) followed by oleic acid (10.4%), linoleic acid (9.6%), γ-terpinene (2.6%), p-cymene (1.6%), palmitic acid (1.6%), and xylene (0.1%). Moreover, the oil exhibited a broad spectrum of fungitoxic behavior against all tested fungi such as Aspergillus niger, Aspergillus flavus, Aspergillus oryzae, Aspergillus ochraceus, Fusarium monoliforme, Fusarium graminearum, Pencillium citrium, Penicillium viridicatum, Pencillium madriti, and Curvularia lunata as absolute mycelial zone inhibition was obtained at a 6-µL dose of the oil. However, the acetone extract showed better antioxidative activity for linseed oil as compared with synthetic antioxidants such as butylated hydroxyl toluene and butylated hydroxyl anisole.